2020
DOI: 10.21037/apm.2020.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Endostar improved efficacy of concurrent chemoradiotherapy with vinorelbine plus carboplatin in locally advanced lung squamous cell carcinoma patients with high serum Lp(a) concentration

Abstract: Background: The role of vascular targeting therapy combined with concurrent chemoradiotherapy (CRT) has produced many inconsistent results in locally advanced non-small-cell lung cancer (NSCLC), especially in lung squamous cell carcinoma (LSCC). Lipoprotein (a) [Lp(a)] may be critical in the development of tumor angiogenesis, and its levels are individualized and determined genetically. This study aimed to determine whether Lp(a) is correlated with effects of recombinant human endostatin (Endostar) combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In addition, the incidence of radiation pneumonia, radiation esophagitis, bone marrow depression, nausea, and vomiting were not increased in the Endostar combined with chemoradiotherapy group, which was consistent with previous studies (44,45) . The non-significant differences may be attributed to the low incidence of AEs, and the power was not enough to detect the potential differences.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the incidence of radiation pneumonia, radiation esophagitis, bone marrow depression, nausea, and vomiting were not increased in the Endostar combined with chemoradiotherapy group, which was consistent with previous studies (44,45) . The non-significant differences may be attributed to the low incidence of AEs, and the power was not enough to detect the potential differences.…”
Section: Discussionsupporting
confidence: 91%
“…With further research, antiangiogenic therapy has also been found to repair the vascular structure and normalize function, which is called vascular normalization [ 14 ]. This phenomenon has been regarded as an important treatment strategy and manifested an ideal therapeutic efficacy in various advanced tumours when combined with chemotherapy [ 15 , 16 ]. Endostar (YH-16) is a novel recombinant human endostatin expressed and purified in Escherichia coli [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that endostatin levels in fibrosis cannot effectively reduce fibrosis, suggesting a “blunted” anti-fibrotic response. Full-length recombinant endostatin, with or without an amino-terminal nonamer, has been studied in the clinical setting for anti-angiogenic properties against various cancers, including gastric, nasopharyngeal, glioblastoma multiforme, lung–brain metastases, and two different lung cancers [ 47 , 48 , 49 , 50 , 51 , 52 ]. Endostatin has also ameliorated bleomycin-induced fibrosis in rats, CCl 4 -induced liver fibrosis in mice, hypertrophic scar formation in rabbit ears, and renal injury in streptozotocin diabetic rats [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%